The burden of inappropriate birth weight on neonatal survival in term newborns: a population-based study in a middle-income setting - Konstantyner, Tulio; Areco, Kelsy Catherina Nema; Bandiera-Paiva, Paulo; Marinonio, Ana Sílvia Scavacini; Kawakami, Mandira Daripa; Balda, Rita de Cássia Xavier; Miyoshi, Milton Harumi; Sanudo, Adriana; Costa-Nobre, Daniela Testoni; de Freitas, Rosa Maria Vieira; Morais, Liliam Cristina Correia; Teixeira, Monica La Porte; et al. (Frontiers in Pediatrics, 2023)
Introduction: Neonatal deaths are mainly associated with complications of prematurity, intrapartum asphyxia, and neonatal infections. Inappropriate birth weight also affects neonatal survival in ways that may differ according to gestational age at birth, particularly in developing countries. The purpose of this study was to test the association between inappropriate birth weight and neonatal death in term live births. Methods: This is a cohort study with all term live births from 2004 to 2013 in Sao Paulo State, Brazil. Data were retrieved with the deterministic linkage of death and birth certificates. The definition of very small for gestational age (VSGA) and very large for gestational age (VLGA) used the 10th percentile of 37 weeks and the 90th percentile of 41 weeks + 6 days, respectively, based on the Intergrowth-21st. We measured the outcome in terms of time to death and the status of each subject (death or censorship) in the neonatal period (0-27 days). Survival functions were calculated using the Kaplan-Meier method stratified according to the birth weight for gestational age (normal, very small or very large). The adjusted analysis of proportional hazard ratios was carried out using multivariate Cox regression. Results: Among 5,141,681 births, there were 6,186 neonatal deaths (rate: 12.03/10,000). The prevalence rates of VSGA and VLGA were 1.77% and 2.74% live births, respectively. The adjusted Cox regression showed a significant increase in mortality risk for VSGA infants (HR=4.25; 95% CI: 3.89; 4.65), independent of sex, 1-minute Apgar score and five maternal factors. Discussion: Birth-restricted weight approximately quadrupled the risk of neonatal death of term live births as a function of time in Sao Paulo State. The prevention of fetal growth retardation through adequate prenatal care, which supposedly includes controlling its risk, potentially contributes to the reduction of neonatal deaths in term live births.